2017
DOI: 10.3390/molecules22081338
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Honeys from Different Geographical and Botanical Origins: A 4-Year Stability Study Regarding Quality Parameters and Antioxidant Activity

Abstract: Portuguese honeys (n = 15) from different botanical and geographical origins were analysed regarding their quality parameters (diastase activity, hydroxymethylfurfural content, moisture and pH), colour (L*, a*, b*) and antioxidant profile (total phenolics content, total flavonoids content, DPPH• scavenging activity, and ferric reducing power). The samples were analysed fresh and after 4-years of storage (at 25 °C and protected from light). The hydroxymethylfurfural content and diastase activity of the fresh sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
8
29
1
Order By: Relevance
“…In relation to the dark colour of heather honey, this is probably due to the contribution of chestnut in its pollen spectrum. Even though one heather honey sample was used in the study, this preliminary finding in nature agrees with the results of Soares et al [21], involving heather honey produced in North and Centre Portugal (Vila Real, Bragança, Chaves, Boticas, Lousã, Penamacor, Vila Nova de Foz Côa and Viseu). In addition, greenish (negative a * values) and yellow components (positive b * values) (pigments) were present in all honey samples analysed in conformity with the aforementioned work [21].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In relation to the dark colour of heather honey, this is probably due to the contribution of chestnut in its pollen spectrum. Even though one heather honey sample was used in the study, this preliminary finding in nature agrees with the results of Soares et al [21], involving heather honey produced in North and Centre Portugal (Vila Real, Bragança, Chaves, Boticas, Lousã, Penamacor, Vila Nova de Foz Côa and Viseu). In addition, greenish (negative a * values) and yellow components (positive b * values) (pigments) were present in all honey samples analysed in conformity with the aforementioned work [21].…”
Section: Resultssupporting
confidence: 88%
“…The CIELAB system uses three parameters to evaluate colour in foodstuffs: (i) colour parameter L* corresponds to the degree of brightness; (ii) colour parameter a* (positive values) corresponds to the degree of redness and when a * shows negative values to the degree of greenness; and (iii) parameter b * corresponds to yellowness of colour (when positive) and to blueness of colour (when negative). What is remarkable is that the units within the L* , a* , b* system may provide equal perception of the colour difference to a human observer [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in accord to the difference between the honey concentrations, undiluted (100% concentrations) were the most effective. Several authors have reported that different honey types vary substantially in the potency of their antibacterial activities, probably attributed to the natural variations in floral sources of nectar and geographical origins or chemical composition [27][28][29]. Likewise, the results generated from this study may be due to the collection of the representative samples of honey from different geographical locations in Libya.…”
Section: Growth Of Proteus Mirabilis In Nutrient Broth With the Incormentioning
confidence: 68%
“…It is known that diastase activity is low and HMF value is high in heated honey [60,61]. Even though the enzyme activity is much more variable than the HFM value of a honey, they are both used for the selection of appropriate processing and packaging techniques among technological applications of natural honey [62].…”
Section: Honey Composition and Antioxidant Activitymentioning
confidence: 99%